Model Pembelajaran Edutainment Melalui Media Gambar 3 Dimensi dalam Mengembangkan Konten Pembelajaran di Madrasah Ibtidaiyah Darul Ulum Curahdami Bondowoso - Zakiyah BZ; Firdausyiyah Firdausyiyah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The main objective of this study was to determine the effectiveness of edutainment learning utilizing 3-dimensional imagery as a medium for educational content creation at MI Darul Ulum Curahdami Bondowoso. Using a qualitative approach with a specially selected phenomenological design, this research targeted key stakeholders, including the principal, the fifth grade teacher, and a group of 10 MI Darul Ulum students. The methodological arsenal consisted of interview sessions, careful observation, and systematic documentation. The researcher found that the edutainment learning model, seamlessly integrated with 3-dimensional imagery for content development, has a great ability to foster a stimulating and enjoyable learning environment, especially in the field of early childhood education. This phenomenon was closely related to the high enthusiasm that students show when encountering visually appealing and captivating images during the learning process. The study underscores implications that require ongoing guidance and evaluative action by educators. This is important to understand the nuances of the dynamics edutainment learning model implemented and measuring the tangible improvements in the students' overall learning experience.